2003
DOI: 10.1677/jme.0.0310157
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain human chorionic gonadotropin analogs containing the determinant loop of the beta-subunit linked to the alpha-subunit

Abstract: Human chorionic gonadotropin (hCG) is a member of the family of glycoprotein hormones containing a common α-subunit and distinct β-subunits that confer hormonal specificity. hCG binds to the relatively large ectodomain of the human luteinizing hormone receptor (hLHR), a member of the G protein-coupled receptor superfamily, leading to increased intracellular production of cAMP. Using protein engineering, two miniaturized versions of hCGβ have been separately fused to the N-terminus of the α-subunit to give N-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Parallel studies using yoked hCG-FSHR and hCG-TSHR showed that each of the receptors could be activated by hCG, albeit to a small extent with FSHR (Schubert et al, 2003). This model system was also used with yoked α-LHR and yoked hCGβ-LHR to show that the individual subunits are incapable of activating LHR under conditions mimicking high concentrations (Narayan et al, 2002); likewise, yoked versions of minimized forms of hCGβ fused to α-LHR identified minimal responses at best (Schubert and Puett, 2003). This system has also been used to prepare and characterize soluble yoked hCG-LHR ECD C-terminal truncation complexes for circular dichroic spectroscopy in which it was demonstrated that secondary structure is lost as the hinge region is removed (Fralish et al, 2003).…”
Section: Structure and Structure-function Relationships Of Lhrmentioning
confidence: 99%
“…Parallel studies using yoked hCG-FSHR and hCG-TSHR showed that each of the receptors could be activated by hCG, albeit to a small extent with FSHR (Schubert et al, 2003). This model system was also used with yoked α-LHR and yoked hCGβ-LHR to show that the individual subunits are incapable of activating LHR under conditions mimicking high concentrations (Narayan et al, 2002); likewise, yoked versions of minimized forms of hCGβ fused to α-LHR identified minimal responses at best (Schubert and Puett, 2003). This system has also been used to prepare and characterize soluble yoked hCG-LHR ECD C-terminal truncation complexes for circular dichroic spectroscopy in which it was demonstrated that secondary structure is lost as the hinge region is removed (Fralish et al, 2003).…”
Section: Structure and Structure-function Relationships Of Lhrmentioning
confidence: 99%
“…Several reports have shown that single-chain variants of glycoprotein hormones with C terminus of the ␤-subunit fused to the N terminus of the ␣-subunit display bioactivities comparable with those of the corresponding heterodimers (27)(28)(29)(30)(31). However, the relative position of the two subunit does not appear to be important for generation of a biologically active molecule (13).…”
Section: Discussionmentioning
confidence: 99%